Introduction to the issue on green translation: How to make it finally happen? - Niko Jaakkola; Riccardo Rovelli (EconPol Forum, 2023)
The Green Transition is in every country's national interest. 'Business-as-usual' is no longer possible; the alternative is a future with costly climate impacts. The Green Transition requires public investments and a sizeable increase in public debt. Strong and coordinated policy signals and actions arerequired to shape expectations, and to thus avoid unnecessary delays and irreversible costs. Economists should promote an interdisciplinary assessment on the growth implications of the Green Transition.The transition will be more politically acceptable if seen to involve "green and inclusive growth" rather than stagnation.
Keywords: 330